NEW METHODS DEVISED FOR TREATING FROZEN SOIL (NUVOE METODY RAZRABOTKI MERZLYKH GRUNTOV) - Emelyanov,U. (1968)
An experimental verification of the effectiveness of block method treatment of frozen soil (small and large blocks) was carried out. (Author) Trans. of mono. Na Stroikakh Rossii, Moscow, 1968, p13-14.